Hand to Mouth in a Neandertal: Right-Handedness in Regourdou 1 - Volpato, Virginie (Public Library of Science, 2012)
We describe and analyze a Neandertal postcranial skeleton and dentition, which together show unambiguous signs of right-handedness. Asymmetries between the left and right upper arm in Regourdou 1 were identified nearly 20 years ago, then confirmed by more detailed analyses of the inner bone structure for the clavicle, humerus, radius and ulna. The total pattern of all bones in the shoulder and arm reveals that Regourdou 1 was a right-hander. Confirmatory evidence comes from the mandibular incisors, which display a distinct pattern of right oblique scratches, typical of right-handed manipulations performed at the front of the mouth. Regourdou's right handedness is consistent with the strong pattern of manual lateralization in Neandertals and further confirms a modern pattern of left brain dominance, presumably signally linguistic competence. These observations along with cultural, genetic and morphological evidence indicate language competence in Neandertals and their European precursors.